The Capiz Sugar Central, Inc. its history and role as a miller, an employer, and a trader in a contemporary setting. - Napalinga, John Mitchell Ortiz (2006.)
This study concerns the historical development of the Capiz, Sugar Central, Inc. as well as its role as a miller, an employer, and a trader based on its actual operations. Its objectives were: 1.) To know the historical background of the sugar industry in Pilar, Capiz before the establishment of Central Azucarera of Central Azucarera de Pilar (former name of Capiz Sugar Central), 2.) To know how Central Azucarera de Pilar was estalished in Crop Year (CY) 1923-1994, 3.) To know the historical development of Central Azucarera de Pilar, its transition into Capiz Sugar Central, Inc. up to the present, 4.) To identify and analyze the role of Capiz sugar Central as an employer, as a miller, and as trader, and 5.) To enumerate and examine the services and benefits extended by CSC to its employees and sugar planters., To achieve the given objectives, the researcher conducted an interview with the local government officials, sugar central employees, sugar planters, and other reliable informants. The researcher likewise conducted research at the UPV library and at the Center for West Visayan Studies for secondary data and related literature. With this course of action, it was found out that the sugar industry in the locality was started upon installation of muscuvado sugar mill in the late 1890's. It was established by Elizaldes and named Central Azucarera de Pilar in 1924. Several measures were also applied by the Elizalde s to expand its milling district and improve its production. Despite such efforts, the Elizaldes suffered financial crisis that the modern mill that was acquired in 1980 through the loan from the bank was foreclosed. In 1989, the mill was acquired by the Uygongcos through bidding, which made the Elizaldes and Uygongcos partners in business. In 1994, the Uygongcos completely owned the sugar central by buying out all the properties of the Elizaldes and renamed it as the Capiz Sugar Central, Inc. The Capiz Sugar Central has been found to be improving its efficiency as well as its production as a miller. It is also environmentally responsible by ensuring the proper disposal of its industrial wastes. As an employer, it exerts effort by providing all possible benefits and services to its employees to gain loyalty. With the interviews conducted from its employees, it was verified indeed, the sugar central is a good provider for them as an employer. As a trader, The Capiz Sugar Central buys and sells its shares in production. It also offers financial assistance to sugar planters for mutual gains. Thus it is concluded that the historical development of the Capiz Sugar Central, Inc. is dependent on the historical events of a particular time. It has also effectively served its functions as a miller, an employer and a trader, thereby serving as key indicators on how it has survived through time.
Research Paper (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Capiz Sugar Central